Infant Dietary Exposures to Sweetness and Fattiness Increase during the First Year of Life and Are Associated with Feeding Practices. Issue 11 (12th October 2016) - Yuan, Wen Lun; Lange, Christine; Schwartz, Camille; Martin, Christophe; Chabanet, Claire; de Lauzon-Guillain, Blandine; Nicklaus, Sophie
Abstract: Background: Taste is a strong determinant of food intake. Previous research has suggested that early taste exposures could influence preferences and later eating behavior, but little is known about the factors related to this. Objectives: The aims of this study were to describe infants' exposure to sweetness and fattiness and to examine whether maternal and infant characteristics and feeding practices are related to these exposures in participants from the OPALINE [Observatoire des Préférences Alimentaires du Nourrisson et de l'Enfant (Observatory of Infant and Child Food Preferences)] cohort study. Methods: Food consumption frequency was assessed with a 7-d food record completed monthly over the first year. Dietary taste exposure was defined by the consumption frequency of each food multiplied by the intensity of its taste, summed over all foods. The daily sweetness exposure (SweetExp) and fattiness exposure (FatExp) were calculated at 3–6, 7–9, and 10–12 mo of age for 268 infants from complementary feeding initiation (CFI) to 12 mo. Associations between taste exposure and potential factors were tested by multiple linear regressions. Results: Both FatExp and SweetExp increased from 3–6 mo to 10–12 mo (mean ± SD: 7.5 ± 2.3 to 12.2 ± 2.5 and 6.8 ± 2.8 to 14.7 ± 4.1, respectively). Breastfeeding duration ≥6 mo was associated with higher SweetExp at all ages, with a decreasing β [β (95% CI): 2.6 (1.8; 3.4) at 3–6 mo and 1.3 (0.1; 2.4) at 10–12 mo]. CFI at <6 mo was associated with higher SweetExp at all ages but with higher FatExp only at 3–6 mo. Higher SweetExp and FatExp were associated with a higher use of all complementary food types. Boys were more likely to be exposed to SweetExp at 10–12 mo and to FatExp at 3–6 mo and 10–12 mo than were girls. Maternal higher education attainment and return to work after 6 mo were linked with higher FatExp and higher FatExp and SweetExp, respectively. Conclusion: SweetExp and FatExp increased from CFI until 12 mo and were associated with feeding practices in OPALINE infants. Studying early taste exposure longitudinally should provide new insights regarding the development of food preferences.